Association Between Furosemide Exposure and Clinical Outcomes in a Retrospective Cohort of Critically Ill Children - Dai, Xiaomei; Chen, Jiao; Li, Wenjing; Bai, Zhenjiang; Li, Xiaozhong; Wang, Jian; Li, Yanhong (Frontiers in Pediatrics, 2021)
Objective: Furosemide is commonly prescribed in critically ill patients to increase the urine output and prevent fluid overload (FO) and acute kidney injury (AKI), but not supported by conclusive evidence. There remain conflicting findings on whether furosemide associates with AKI and adverse outcomes. Information on the impact of furosemide on adverse outcomes in a general population of pediatric intensive care unit (PICU) is limited. The aim of the cohort study was to investigate the associations of furosemide with AKI and clinical outcomes in critically ill children. Study design: We retrospectively reviewed a cohort of 456 critically ill children consecutively admitted to PICU from January to December 2016. The exposure of interest was the use of furosemide in the first week after admission. FO was defined as ≥5% of daily fluid accumulation, and mean FO was considered significant when mean daily fluid accumulation during the first week ≥5%. The primary outcomes were AKI in the first week after admission and mortality during PICU stay. AKI diagnosis was based on Kidney Disease: Improving Global Outcomes criteria with both serum creatinine and urine output. Results: Furosemide exposure occurred in 43.4% of all patients (n=456) and 49.3% of those who developed FO (n=150) in the first week after admission. Patients who exposed furosemide had significantly less degree of mean daily fluid accumulation than those who did not (1.10 [-0.33-2.61]% vs. 2.00 [0.54-3.70]%, P<0.001). There was no difference in the occurrence of AKI between patients who did and did not receive furosemide (22 of 198 [11.1%] vs. 36 of 258 [14.0%], P=0.397). The mortality rate was 15.4% (70 of 456), and death occurred more frequently among patients who received furosemide than among those who did not (21.7% vs. 10.5%, P=0.002). Furosemide exposure was associated with increased odds for mortality in multivariate logistic regression model adjusted for body weight, gender, illness severity assessed by PRISM III score, the presence of mean fluid overload, and AKI stage (AOR 1.95; 95%CI, 1.08-3.52; P=0.026). Conclusion: Exposure to furosemide might be associated with increased risk for mortality, but not AKI, in critically ill children.